ERO and PIC simulations of gross and net erosion of tungsten in the outer strike-point region of ASDEX Upgrade - Hakola, A.; Airila, M. I.; Mellet, N.; Groth, M.; Karhunen, Juuso; Kurki-Suonio, T.; Makkonen, T.; Sillanpää, Heikki; Meisl, G.; Oberkofler, M., ASDEX Upgrade Team (Elsevier, 2017)
We have modelled net and gross erosion of W in low-density . l-mode plasmas in the low-field side strike point region of ASDEX Upgrade by ERO and Particle-in-Cell (PIC) simulations. The observed net-erosion peak at the strike point was mainly due to the light impurities present in the plasma while the noticeable net-deposition regions surrounding the erosion maximum could be attributed to the strong . E ×. B drift and the magnetic field bringing eroded particles from a distance of several meters towards the private flux region. Our results also imply that the role of cross-field diffusion is very small in the studied plasmas. The simulations indicate net/gross erosion ratio of 0.2-0.6, which is in line with the literature data and what was determined spectroscopically. The deviations from the estimates extracted from post-exposure ion-beam-analysis data (∼0.6-0.7) are most likely due to the measured re-deposition patterns showing the outcomes of multiple erosion-deposition cycles.
Keywords: ASDEX Upgrade; Cross-field diffusion; ERO modelling; Particle drifts; PIC simulations; Tungsten erosion